Quantum Information and Computation (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Quantum information and quantum computing are very rapidly developing research directions in recent years. This reprint introduces some of the latest developments in quantum theory, including basic physical theories such as quantum entanglement, and quantum information processing; and applications such as quantum secret key allocation, and several types of quantum algorithms. This reprint is suitable for some researchers or students to read.